2016
DOI: 10.1103/physreve.94.053114
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of initial condition effects on Rayleigh-Taylor instability with acceleration reversals

Abstract: The influence of initial conditions on miscible incompressible baroclinically driven Rayleigh-Taylor instability undergoing non-uniform acceleration is explored computationally using an Implicit Large Eddy Simulation (ILES) technique. We consider the particular case of evolution during multiple reversals of acceleration direction, where the flow is alternately statically stable or unstable. In the unstable phase, the flow is driven by the baroclinic release of potential energy, whereas in the stable phase, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
1
25
1
Order By: Relevance
“…In the same year, Zhou et al used a numerical method to analyze the statistics of the kinetic energy and thermal energy dissipation rate of 2D RT turbulence [ 28 ]. Aslangil et al used an implicit large eddy simulation technique to analyze the effect of initial conditions on the stability of miscible incompressible barotropic pressure driven RT under non-uniform acceleration conditions [ 29 ]. In 2018, Zhang et al studied the instability of 2D and 3D multimode ablation RT.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Zhou et al used a numerical method to analyze the statistics of the kinetic energy and thermal energy dissipation rate of 2D RT turbulence [ 28 ]. Aslangil et al used an implicit large eddy simulation technique to analyze the effect of initial conditions on the stability of miscible incompressible barotropic pressure driven RT under non-uniform acceleration conditions [ 29 ]. In 2018, Zhang et al studied the instability of 2D and 3D multimode ablation RT.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, increasing attention has been given in recent years to Rayleigh-Taylor instability undergoing variable acceleration (see, in particular, Refs. [15][16][17][18][19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work compared implicit large eddy simulations (ILES) [23] with previously unpublished experimental results (A ¼ 0.48) [24], and it was concluded that ILES with a broadband initial perturbation spectrum matched the experiments. Some more recent work has focused on the sensitivity of future development to initial conditions [19] and has found that structural features of the initial condition persist through to the second acceleration. Another recent study also examined the sensitivity to duration of deceleration [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, one of the most important numerical simulations conducted was the 3072 3 direct numerical simulation of multimode RTI by Cabot and Cook [22]. More recently, the numerical investigations of Aslangil et al [23] and Ramaprabhu et al [24] have focused on the effects of time varying acceleration profiles. Turbulent RTI has been described as a process of self-similar mixing layer growth resulting from the interaction of bubbles of different length scales.…”
Section: Introductionmentioning
confidence: 99%